Unlocking student potential through engagement: exploring the learning outcomes and career intentions of medical students transferring from junior colleges to undergraduate universities in China - Ziyue Shen; Yunbo Liu; Hongbin Wu (BMC Medical Education)
Abstract Several studies have examined whether students transferring from junior colleges have a sufficient educational foundation to succeed at the university level. However, a controversy has arisen because prior studies offer conflicting results. Moreover, these studies have not looked at medical transfer students. This study examined the differences in learning outcomes and career intentions (CI) between transfer students and those who began at medical universities in China (native students), focusing on student engagement. The sample data, from the 2020 China Medical Student Survey, included fifth-year (graduate year) medical students from 39 universities (6,712 native and 1,582 transfer students). A conceptual framework was constructed using the input-environment-output model and student engagement theory. Engagement was categorized into behavioral, emotional, and cognitive dimensions. The analysis encompassed t-tests, chi-square tests, multivariable linear and logistic regressions, Shapley value modeling, and path analysis. The results showed that a significantly higher proportion of transfer students came from disadvantaged backgrounds and had lower pre-entry abilities, although their self-reported engagement was higher. Thus, engagement contributed to their ability to catch up in terms of learning outcomes, with emotional engagement having significant direct and indirect positive associations with learning outcomes and CIs. Ultimately, there were no significant differences in learning outcomes and CIs between transfer and native students. The findings suggest that transfer students are more engaged despite their disadvantages and show no significant weakness in their learning outcomes or CI. This underscores the importance of preserving and enhancing access to undergraduate studies for Chinese medical students in junior colleges, thereby promoting educational equity.